The Use Of The Erga Omnes Principle In The Implementation Of Decisions Of The State Administrative Court (PTUN) With Permanent Legal Power - Laritmas, Selfianus; Gede Yusa, I; Rosidi, Ahmad (CV. Inara, 2022)
Legal regulation The role of the State Administrative Court in the practice of settling government administration in Indonesia needs to be properly regulated, because in the implementation of the Administrative Court decisions according to Article 116 of Law no. 51 of 2009 concerning the Second Amendment to Law No. 5 of 1986 is a regulation regarding forced money which is not clear and there is no final settlement of a decision that has permanent legal forcethe execution cannot be carried out properly, and the absence of an executive or foundational institution strong law causes the decision of the State Administrative Court to have no power force. Even the State Administrative Court Law does not regulate firmly and clearly regarding the issue of the coercive power of the State Administrative Court's decision, so that in the implementation The decision really depends on the good faith of the State Administration Agency or Official in obey the law. This situation is quite alarming, because the principle of justice is State Administration, to put juridical control in the government to be lost meaning in the Indonesian constitutional bureaucratic system even though the decision should bind the disputing parties and have executive power when they already have a decision that has permanent legal force, according to the legal principle Erga omnes states thatThe decision of the State Administrative Court is publicly binding, not only binding on the disputing parties. This is a consequence of the nature of the state administrative dispute which is a public legal dispute, so that the Administrative Court Decision must bind all interested parties and have the obligation to comply with every decision;This research analyzes the problem, How about The existence of the Implementation of Administrative Court Decisions in the law enforcement system? And Has the execution of the Administrative Court Decision been effective in the law enforcement system. The research methodology used in this study is normative juridical with the approach used is the Statute Approach and the Case Approach, the approach carries out an assessment of laws and regulations related to the central theme of research with the procedure for collecting legal materials. Both Primary and secondary legal materials are collected based on the topic of the problem that has been formulated based on the Legislation which is reviewed comprehensively to provide new legal ideas for legal reform.